Diagnostic SOX10 gene signatures in salivary adenoid cystic and breast basal-like carcinomas - Sergey V. Ivanov; Alex Panaccione; Daisuke Nonaka; Manju L. Prasad; Kelly L. Boyd; Brandee Brown; Yan Guo; Andrew Sewell; Wendell G. Yarbrough (2013)
Salivary adenoid cystic carcinoma (ACC) is an insidious slow-growing cancer with the propensity to recur and metastasise to distant sites. Basal-like breast carcinoma (BBC) is a molecular subtype that constitutes 15–20% of breast cancers, shares histological similarities and basal cell markers with ACC, lacks expression of ER (oestrogen receptor), PR (progesterone receptor), and HER2 (human epidermal growth factor receptor 2), and, similar to ACC, metastasises predominantly to the lung and brain. Both cancers lack targeted therapies owing to poor understanding of their molecular drivers. Gene expression profiling, immunohistochemical staining, western blot, RT-PCR, and in silico analysis of massive cancer data sets were used to identify novel markers and potential therapeutic targets for ACC and BBC. For the detection and comparison of gene signatures, we performed co-expression analysis using a recently developed web-based multi-experiment matrix tool for visualisation and rank aggregation. In ACC and BBC we identified characteristic and overlapping SOX10 gene signatures that contained a large set of novel potential molecular markers. SOX10 was validated as a sensitive diagnostic marker for both cancers and its expression was linked to normal and malignant myoepithelial/basal cells. In ACC, BBC, and melanoma (MEL), SOX10 expression strongly co-segregated with the expression of ROPN1B, GPM6B, COL9A3, and MIA. In ACC and breast cancers, SOX10 expression negatively correlated with FOXA1, a cell identity marker and major regulator of the luminal breast subtype. Diagnostic significance of several conserved elements of the SOX10 signature (MIA, TRIM2, ROPN1, and ROPN1B) was validated on BBC cell lines. SOX10 expression in ACC and BBC appears to be a part of a highly coordinated transcriptional programme characteristic for cancers with basal/myoepithelial features. Comparison between ACC/BBC and other cancers, such as neuroblastomaand MEL, reveals potential molecular markers specific for these cancers that are likely linked to their cell identity. SOX10 as a novel diagnostic marker for ACC and BBC provides important molecular insight into their molecular aetiology and cell origin. Given that SOX10 was recently described as a principal driver of MEL, identification of conserved elements of the SOX10 signatures may help in better understanding of SOX10-related signalling and development of novel diagnostic and therapeutic tools.